Cultural Strategy in Practice: A Case Study of Iranian Americans in Los Angeles - Hirbod Norouzianpour; David Weiss (Cadernos de Arte Pública)
We provide an analytic observation of Iranian-Americans in Los Angeles and their strategies to overcome “displacement” and “othering” challenges in a city they now call home. Our focus is on the Iranian community’s efforts to manifest itself by investing in a specific manifestation of “cultural strategy” in the form of a permanent art installation—the Freedom Sculpture—and the underlying need for the community to make such an investment in the current political atmosphere. We conclude the article by considering the project’s outcomes, including the impact on the greater Los Angeles community. This sculpture creates an opportunity for Iranian-Americans to publicly tell their stories and talk about who they are; it is a medium through which Iranian-Americans can start a dialogue with other citizens and thereby achieve greater integration. Accordingly, the role of the built environment in fortifying a sense of belonging is discussed, including ways that the environment can help new arrivals overcome certain aspects of an identity crisis.